Streptococcus intermedius promotes synchronous multiple primary lung cancer progression through apoptosis regulation - Deng, Yi; Dong, Zhi Xiang; Yang, Gao Hua; Krimsky, William S.; Tai, Yong Hang; Peng, Hao; Huang, Gui Ting; Xu, Jia Xin; Sarkar, Saiyad A.; Peng, Jun; Qian, Kai (Frontiers in Immunology, 2025)
BackgroundDysbiosis of the lung microbiome can contribute to the initiation and progression of lung cancer. Synchronous multiple primary lung cancer (sMPLC) is an increasingly recognized subtype of lung cancer characterized by high morbidity, difficulties in early detection, poor prognosis, and substantial clinical challenges. However, the relationship between sMPLC pathogenesis and changes in the lung microbiome remains unclear.MethodsIn this study, 16S rRNA sequencing was performed on clinical samples to analyze lung microbiome composition. Real-time quantitative PCR (qPCR) was used to quantify bacterial abundance in lung tissues. In addition, flow cytometry was conducted to evaluate cell cycle progression and apoptosis in lung tumor cells.ResultsClinical cohort studies demonstrated that sMPLC occurrence is associated with disturbances in the lung microbiome. Notably, Streptococcus intermedius was enriched in the lungs of sMPLC patients compared with non-tumor controls and accumulated preferentially in tumor tissues. S. intermedius shortened the cell cycle and inhibited apoptosis in lung cancer cells. Analyses of oral and gut microbiomes in different patient cohorts revealed a strong correlation between oral microbiome imbalances and lung microbiome composition in sMPLC patients.ConclusionsThese findings characterize the lung microbiota in sMPLC and identify S. intermedius as a potentially influential bacterial strain. This study provides significant new insights into the diagnosis and treatment of sMPLC.